2019
DOI: 10.17763/1943-5045-89.4.525
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Special Education Identification and Placement: Evidence Across Three States

Abstract: In this article, Todd Grindal, Laura Schifter, Gabriel Schwartz, and Thomas Hehir examine race/ethnicity differences in students' special education identification and subsequent placement in segregated educational settings. Using individual-level data on the full population of K–12 public school students in three states, the authors find that racial and ethnic disparities in identification persist within income categories and are stronger for those disabilities that are typically identified in a school setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 25 publications
6
36
0
1
Order By: Relevance
“…Although not recommended by many in the field, such research indicates these practices continue to happen. In addition, once labeled as disabled, Black and Latinx children are disproportionately placed in segregated settings compared to white children with dis/abilities, regardless of family income (Grindal et al, 2019). Segregated placements often limit children to curriculum focused on their perceived deficits which may lead to their future exclusion as the gap between them and “normal” expands (Dudley-Marling & Burns, 2014; Ferri & Bacon, 2011).…”
Section: Using Discrit To Facilitate Justice-driven Inclusive Educatimentioning
confidence: 99%
See 3 more Smart Citations
“…Although not recommended by many in the field, such research indicates these practices continue to happen. In addition, once labeled as disabled, Black and Latinx children are disproportionately placed in segregated settings compared to white children with dis/abilities, regardless of family income (Grindal et al, 2019). Segregated placements often limit children to curriculum focused on their perceived deficits which may lead to their future exclusion as the gap between them and “normal” expands (Dudley-Marling & Burns, 2014; Ferri & Bacon, 2011).…”
Section: Using Discrit To Facilitate Justice-driven Inclusive Educatimentioning
confidence: 99%
“…The singular use of race, home language, and/or socioeconomic status to label children as “at risk” is evidenced in some research examining the effects of comprehensive or multi-tiered intervention models and language interventions (e.g., McLeod et al, 2017; Pentimonti et al, 2017). While such research provides useful information about potential ways to provide and structure supports, by operationalizing “risk” as being static and inherent in the child and/or family (as opposed to social systems and institutionalized practices), it can perpetuate disproportionate labeling of children of Color as having dis/abilities and their subsequent placement in segregated classrooms (Grindal et al, 2019; Wright & Ford, 2016). The latter is allowed by the legal ambiguities imbued in IDEA’s mandate that children be placed in the least restrictive environment (LRE) to the “maximum extent appropriate” (Grindal et al, 2019).…”
Section: Using Discrit To Facilitate Justice-driven Inclusive Educatimentioning
confidence: 99%
See 2 more Smart Citations
“…1 We analyze young people's test scores, measure their beliefs about themselves, and observe their behaviors and comments in classrooms. In the pages of recent issues of Harvard Educational Review (HER) alone, scholars have investigated which youth get identified as gifted (Grindal, Schifter, Schwartz, & Hehir, 2019), how immigrant African youth navigate the college application process (George Mwangi, 2019), and the multiple ways kindergarten teachers respond to student mistakes (Donaldson, 2020). These studies and many others have built crucial knowledge and scholarship about youth and education, and, in line with the particular aim of our journal, helped scholars, practitioners, and policy makers work toward creating a society where all young people have equal opportunities to learn, grow, and thrive.…”
mentioning
confidence: 99%